A Comparative Study of Two In Vivo PET Verification Methods in Clinical Cases - Zhang, Junyu; Lu, Yan; Sheng, Yinxiangzi; Wang, Weiwei; Hong, Zhengshan; Sun, Yun; Zhou, Rong; Cheng, Jingyi (Frontiers in Oncology, 2021)
Purpose Positron emission tomography (PET) range verification is an important method that can help improve the confidence in proton therapy for clinical applications. Two kinds of verification methods are implemented and compared based on clinical cases in this study. Method The study is conducted on 14 breast cancer patients following proton irradiation treatment. Verification is done by calculating the depth error between the numerically predicted values with the measured PET image along the beam direction. Point-based and segment-based methods are applied and compared. The verification results are presented as depth error means and standard deviations in a region of interest (ROI). Results The mean value of the depth error of all 14 cases is within the range of [−3, 3] mm for both point-based and segment-based methods, and only one case result calculated by the point-based method is slightly beyond −3 mm. When comparing the mean depth error from the two methods, the paired t-test result shows that the p-value is 0.541, and the standard deviation of the segment-based method is smaller than that of the point-based method. Conclusion In breast cancer case verification application, point-based and segment-based methods show no significant difference in the mean value of results. Both methods can quantify the accuracy of proton radiotherapy to the millimeter level.